2008
DOI: 10.2976/1.2909080
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic proofreading of gene activation by chromatin remodeling

Abstract: Gene activation in eukaryotes involves the concerted action of histone tail modifiers, chromatin remodellers and transcription factors, whose precise coordination is currently unknown. We demonstrate that the experimentally observed interactions of the molecules are in accord with a kinetic proofreading scheme. Our finding could provide a basis for the development of quantitative models for gene regulation in eukaryotes based on the combinatorical interactions of chromatin modifiers.Comment: 8 pages, 2 Figures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 13 publications
(26 reference statements)
1
30
0
Order By: Relevance
“…In contrast to PCNA, ISWIs thoroughly probe a large number of nucleosomes by a continuous sampling mechanism, thus ensuring that potential targets are reliably identified. Interestingly, ISWI-type remodelers have been proposed to translocate nucleosomes according to a kinetic proof reading scheme, 35,36 which involves the cell cycle was followed by flow cytometry using a FACSCalibur instrument (BD Biosciences) after fixing the cells with ethanol and staining with 0.25 μM TO-PRO3 and an antibody against GFP. Data were analyzed with the software Weasel (WEHI).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to PCNA, ISWIs thoroughly probe a large number of nucleosomes by a continuous sampling mechanism, thus ensuring that potential targets are reliably identified. Interestingly, ISWI-type remodelers have been proposed to translocate nucleosomes according to a kinetic proof reading scheme, 35,36 which involves the cell cycle was followed by flow cytometry using a FACSCalibur instrument (BD Biosciences) after fixing the cells with ethanol and staining with 0.25 μM TO-PRO3 and an antibody against GFP. Data were analyzed with the software Weasel (WEHI).…”
Section: Methodsmentioning
confidence: 99%
“…These modifications directly affect nucleosome dynamics or recruit enzyme complexes required for various functions (Kouzarides 2007). Posttranslational modifications may provide kinetic proofreading to reduce the error rate of gene activation (Blossey and Schiessel 2008). We searched for methylation, acetylation, phosphorylation, and other histone PTMs using UniProt (Wu et al 2006) and using Textpresso with the spatial relationship ontological category followed by manual curation (Muller et al 2004).…”
Section: Mutations Affecting Post-translational Modificationsmentioning
confidence: 99%
“…It has been suggested that both the SWI/SNF and ISWI/ACF chromatin remodelling complexes use an ATP-dependent kinetic proofreading scheme to find the correct nucleosomal substrates on which to act [59,60], in a manner essentially identical to Hopfield's original scheme [61]. In contrast, as mentioned in the Background, nucleosomes have been treated as competing with transcription factors for binding to DNA within the thermodynamic formalism, ignoring the dissipative aspects [18,62].…”
Section: Discussionmentioning
confidence: 99%